In Praise of Cultural Environmental Ethics - Bisong, Peter; Eba, Maxwell-Borjor; Nwogu, Aaron Ogbonnah (Studia Ecologiae et Bioethicae, 2025)
It is now very clear to many that environmental health has degraded to such a degree that it requires urgent attention. Most scholars have understood that the failing health of the environment is mostly due to the wrong way it is being handled by human beings. This realization has necessitated various calls for an environmental ethic that would inspire positive human actions towards the environment. In response to these calls, many environmental ethics have been proposed, most of which are global ethics of human behaviour. While commending these efforts, we argue in this work that global standard setting ethics would not be as effective as relativistic ethics in handling environmental challenges. This is because, it is difficult to set a global ethics that would satisfy all cultural values as to be justifiably binding on all human beings. Culture inspired ethics would most likely provoke more positive activities towards the environment than any global totalizing ethics.